Factors Determining Intranet Usage: An Empirical Study Of Middle Managers In Malaysian Port Industry - Mohd Daud, Norzaidi (2008)
The objectives of this study are to (1) To identify the perception of the middle managers on the affect of Intranet Usage (2) To validate the theoretical framework proposed (3) To examine the relationship between variables and (4) To ascertain the level of impact of the variables on performance.